PENGARUH PEMAHAMAN AKUNTANSI, SISTEM AKUNTANSI KEUANGAN PEMERINTAH DAERAH DAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi pada skpd Kabupaten Indragiri Hilir) - Aniftahudin '; Kamaliah '; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to determine the effect of understanding of accounting to the quality of financial reporting area, the effect of the accounting system of local government finance to the quality of financial reporting area and the influence of information technology areas of the quality of financial reporting area, and to determine the effect of understanding of accounting, financial accounting systems of local government and technology information on the quality of the financial reporting area. This study was included in the quantitative research. The sample is determined by using purposive sampling and sampling for each SKPD using the proportional method. The sample in this study were 81. Data were analyzed using multiple regression with SPSS version 20.0. The results show that understanding of accounting positive effect on quality of financial reporting area, System of financial accounting of local governments positive effect on the quality of regional financial reports, and information technology affects positive on the quality of financial reporting area, and understanding of accounting, financial accounting systems of local government, information technology affect the quality of financial reporting.Keywords : Understanding Accounting, Financial Accounting System of Local Government, Information Technology, and Quality Regions Financial Statements.